Study of complex impedance spectroscopic properties of La(0.7−x)Dy(x)Sr(0.3)MnO(3) perovskite oxides - Debbebi, I. Sfifir (R Soc Open Sci, 2018)
The dysprosium perovskite La(0.7−x)Dy(x)Sr(0.3)MnO(3) (x = 0.00 [LSMO] and 0.03 [LDSMO]) compounds were prepared by the sol–gel reaction and characterized by the X-ray diffraction technique. The electrical conductivity and modulus characteristics of the system have been investigated in the temperature and the frequency range 311–356 K and 209–5 × 10(7) Hz, respectively, by means of impedance spectroscopy. The ac and dc conductivities were studied to explore the mechanisms of conduction of LSMO and LDSMO. The insertion of a small amount of Dy(3+) in the La-site of LSMO perovskite oxide increases the value of the activation energy from 0.2106 to 0.5357 eV and enhances electrical resistivity values for almost two orders of magnitude.